Aquatic Environmental Analysis of the Hematological Profile of Barbonymus altus in the Brantas River, Jombang, East Java - Aang Setyawan Anjasmara; Hertika, Asus Maizar Suryanto; Yanuhar, Uun (Graduate School, Universitas Brawijaya, 2022)
The Brantas River is the longest in East Java. One of the areas included in the flow of the Brantas River is the Jombang Regency. The Jombang Brantas River is used by the community to meet their daily needs in agriculture, plantations, industry, and fishing grounds. The input of waste generated from several community activities will result in the survival of fish in the waters. Fish as a biomarker agent is quite significant in estimating the level of heavy metal pollution. Red Bader Fish (Barbonymus altus) is often found and lives around the Jombang Brantas River. This study aims to determine the condition of the aquatic environment by observing the health of the fish through hematological observations of the Red Bader Fish (B. altus). Sampling was carried out at three stations with three replications every two weeks, which was carried out in February – March 2022 in the Jombang Brantas River. Data analysis used the Canonical Correspondence Analysis (CCA) method as an analytical method to determine the correlation between the dependent variable (hematological profile) and the independent variable (water quality conditions). In this study, the results showed that the water quality at Station 1 and Station 2 was classified as normal, while at Station 3, it was classified as polluted. Data analysis showed that erythrocytes, hemoglobin, and hematocrit had a relationship with temperature, pH, DO, BOD, ammonia, TSS, and TDS in low concentrations. Meanwhile, leukocytes and micronuclei showed a relationship with high concentrations of ammonia, BOD, TDS, and TSS. Keywords: Brantas River, Bader fish (Barbonymus altus), CCA, hematology, water quality.